2022
DOI: 10.1093/stcltm/szab031
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Integration of TRAIL in iPSC-Derived Mesenchymal Stem Cells for Targeted Cancer Therapy

Abstract: Mesenchymal stem cells (MSCs) are a promising cellular vehicle for transferring anti-cancer factors to malignant tumors. Currently, a variety of anti-cancer agents, including the tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), have been loaded into MSCs derived from a range of sources through different engineering methods. These engineered MSCs exhibit enormous therapeutic potential for various cancers. To avoid the intrinsic defects of MSCs derived from tissues and the potential risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Tumor necrosis factor related apoptosis-inducing ligand (TRAIL) is a type II membrane-bound protein capable of inducing apoptosis in various cancer cells. TRAIL-expressing MSCs exhibited directional migration and infiltration toward tumor tissues, extended animal survival and contributed to overcoming drug resistance [489][490][491]. Furthermore, exogenous microRNAs delivered by MSCs also assist in antitumor therapy, which deserves further clinical evaluation [492][493][494].…”
Section: Mscs As Potential Therapeutic Targetmentioning
confidence: 99%
“…Tumor necrosis factor related apoptosis-inducing ligand (TRAIL) is a type II membrane-bound protein capable of inducing apoptosis in various cancer cells. TRAIL-expressing MSCs exhibited directional migration and infiltration toward tumor tissues, extended animal survival and contributed to overcoming drug resistance [489][490][491]. Furthermore, exogenous microRNAs delivered by MSCs also assist in antitumor therapy, which deserves further clinical evaluation [492][493][494].…”
Section: Mscs As Potential Therapeutic Targetmentioning
confidence: 99%
“…However, despite the induction of necrosis in some areas of the tumor, the administration of CIMVs-TRAIL did not induce any significant decrease in the tumor growth rate. Apparently, this level of necrosis induction was not sufficient to influence tumor progression since, in other studies, the percentage of necrotic tissue after TRAIL delivery reached 42% [48]. Additionally, it has been shown that the introduction of vesicles together with tumor cells can more effectively delay the development of the tumor [19].…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have reported that genetically engineered MSCs with TRAIL overexpression could exhibit an inhibitory effect on the growth of some TRAIL-resistant cells, such as ileocecal adenocarcinoma HCT8 cells [47]. Moreover, iPSC-derived MSCs that were site-specifically integrated with TRAIL gene into the genome caused TRAIL-induced apoptosis in resistant lung adenocarcinoma A549 cells and MCF-7 cells in vitro and in vivo [48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The biological interaction between MSC and tumor is complex and enormously debated. Several controversies exist about the potential of MSC to enhance or to even arrest tumorigenicity, because of their double faced behaviour: tumor-tropism (hence tested as vehicles for anticancer genes targeting cancer cells or as enhancement of the CAR-T immunotherapy) [4,5] and immunomodulative features, but also pro-metastatic functions [6][7][8], trans-differentiation into cancer-associated fibroblasts and drug resistance [9] and the parallel ability to overturn the immune system [10][11][12][13], activation of autophagy and neo-angiogenesis [14], therefore contributing to tumor evolution. This discrepancy also includes exosomes-derived MSC, considered both an intriguing therapeutic tool for drug delivery and main biological mediators of several supporting tumor molecular process [15].…”
Section: Introductionmentioning
confidence: 99%